Silent Syntactic Structures in Malay: Copular Clauses - Mustaffa, Amir Rashad (Journal of Modern Languages, 2018)
Phonetic realisation does not absolutely determine whether syntactic structure exists. Certain constructions might lack overt syntax, but once thoroughly examined, show telltale signs of silent syntactic structure. Copular constructions in Malay are certainly one of such constructions as subjects and complements in nonverbal predication are not mediated by a copula; therefore, by Occam’s razor, the simplest analysis would be that there is no structure between the two constituents. This study examines copular clauses in Malay and attempts to substantiate the claim that there is more syntactic structure than meets the eye (or ear) through the use of certain diagnostic tests such as the use of adverbials and auxiliaries, to detect the presence of inflectional and verbal projections. It is found that copular clauses possess both inflectional and verbal layers as it is possible for certain auxiliaries and adverbials to occur in copular clauses in Malay.